Development of Self-Esteem Assessment Instruments for Diabetic Ulcer Patients - Dasuki; Nofrida Saswati; Ade Ulfah Setiawati Putri; Wiwik Rofiqah (NERS Jurnal Keperawatan, 2026)
Poor wound care in patients with diabetic wounds can lead to tissue death, which may require surgical intervention. One example is a foot wound known as a diabetic ulcer. If tissue death occurs in the wound area, surgery is indicated, which can have psychological impacts on the individual. This research aimed to develop a self-esteem assessment instrument for diabetic ulcer patients. The research method that will be carried out is a mixed method with a sequential exploratory design. This research design quantitative research methods that are carried out sequentially. The analysis results of the questionnaire feasibility score showed that the total score obtained by expert 1 was 0.90 and expert 2 was 0.8, included in the very feasible criteria. From the analysis of 38 question items, the results obtained were 35 valid and reliable question items and 3 invalid and unreliable question items. The test was carried out by comparing the calculated r-value of 0.981 for each question with the r-table value of 0.3494. The questionnaire for measuring self-concept in patients with diabetes mellitus wounds is mostly valid and reliable, therefore health workers can use this questionnaire to measure self-concept in patients with diabetes mellitus who have wounds.